Viscosity of Mono vs Hybrid Nanofluids: Measurement and Comparison. Issue 1 (July 2020) - Fadzli, Khairil; Abdullah, MZ; Mazlan, NM; Mohamed, AR; Ahmed Janvekar, Ayub; Nasir, FM
Abstract: The authors aimed to look into the viscosity investigation of mono and hybrid Aluminium Oxide/Silicon Oxide (Al2O3/SiO) based nanofluids. The viscosity methods were carried out for mono nanofluids as well as hybrid nanofluid, which are suspended in base fluid (water). Both mono and hybrid nanofluids of Al2O3/SiO were developed in concentration, which vary from 0.01% to 1.00%. The methodology invoked for viscosity measurement was done by spindle rotation technique, which uses Anton Paar RheolabQC rotational rheometer at temperatures of 30 - 70 ° C. The results imply that viscosity of nanofluids was directly proportional to volume concentration and temperature.